2000
DOI: 10.1046/j.1365-2826.2000.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Blockade of the Mineralocorticoid Receptor Impairs Hypothalamic‐Pituitary‐Adrenal Axis Expression of Habituation

Abstract: The present study investigated the role of mineralocorticoid receptors (MR) and glucocorticoid receptors (GR) in the expression of habituation of the hypothalamic-pituitary-adrenal (HPA) axis response to stress. Male rats were restrained for 1 h per day for six consecutive days. On day 6, 1 h prior to restraint stress, both restraint-naive and repeatedly restrained rats were injected s.c. with either vehicle (propylene glycol) or one of three corticosteroid receptor antagonist treatments: selective MR antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 45 publications
7
78
1
1
Order By: Relevance
“…This hypothesis is supported by the evidence that blockade of central mineralocorticoid receptors can prevent habituation of the corticosterone response to repeated restraint (Cole et al 2000). Our data suggest that the effects of AVPR1B antagonist and chronic stress .…”
Section: Discussionsupporting
confidence: 78%
“…This hypothesis is supported by the evidence that blockade of central mineralocorticoid receptors can prevent habituation of the corticosterone response to repeated restraint (Cole et al 2000). Our data suggest that the effects of AVPR1B antagonist and chronic stress .…”
Section: Discussionsupporting
confidence: 78%
“…The corticosterone responses to restraint stress were elevated for the first 4 wk, after which responses habituated. Thus, intermittent exposure to restraint stress for an extended time causes habituation of corticosterone responses as is commonly seen with repeated exposure to the same type of stress (2,15,33,34,65). However, we (5) have previously shown that this is accompanied by sustained reductions in food intake and inhibition of growth hormone, illustrating persistent effects of chronic stress independent of corticosterone responses.…”
Section: Animalsmentioning
confidence: 73%
“…Interestingly, the present results raise the possibility of a habituation of the hypothalmo-pituitaryadrenal (HPA) axis in response to repeated mild stress. The habituation of HPA axis activation has been previously shown after repeated exposure to restraint (Hauger et al, 1990;Cole et al, 2000), cold (Bhatnagar et al, 1995), noise (Armario et al, 1986), water immersion (De Boer et al, 1990), and repeated handling (Dobrakovova et al, 1993).…”
Section: Discussionmentioning
confidence: 88%